KORELASI PENGGUNAAN PESAN ANTAR MAKANAN ONLINE, PENGETAHUAN KONSUMSI GULA GARAM DAN LEMAK DENGAN FREKUENSI JAJAN DI SMA JAKARTA UTARA - Nugroho Jati, Mateus Bagas; Rasmada, Sada (Jurnal Gizi dan Pangan Soedirman, 2023)
The factors for someone to snack on at this time are very varied, some come from inside and outside oneself. This study aims to analyze the relationship between online food delivery, and knowledge of GGL consumption with the frequency of snacks in SMA North Jakarta. This study uses a cross-sectional design. Respondents were adolescents aged 16-18 years as many as 89 people. Research respondents were selected by purposive sampling technique. Data analysis includes univariate and bivariate using Spearman's rank. The results of the univariate showed that high school students in North Jakarta often ate snacks (87.6%). The dish that is often ordered is fried chicken (87,6%). The snack food that is often ordered is french fries (37,08%). The most frequently ordered drink is tea (34,83%). Furthermore, they often used online food delivery (56.2%). The application that is often used is GoFood (70,79%) knowledge related to GGL consumption was dominated by moderate (62.9%). The results of the bivariate test showed a correlation between ordering online food delivery with frequency of snack (r = 0.219; p = 0.039). Meanwhile, there was no correlation between knowledge of GGL consumption and snack frequency (p = 0.179).